Potensi Fungi Endofit dari Daun Sirih (Piper Betle L.) sebagai Alternative Pencarian Senyawa Antibiotik terhadap Bakteri Penyebab Infeksi - Marhamah Marhamah; Muh Danial Fajri; Lola Tulak Rerung (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Infections and antibiotic resistance pose significant challenges to global healthcare. This study aims to evaluate the antibacterial potential of endophytic fungi isolated from betel leaves (Piper betle L.) against Staphylococcus aureus and Staphylococcus epidermidis. The research involved isolating endophytic fungi using Potato Dextrose Agar (PDA), purifying the isolates, and testing their antibacterial activity through the disk diffusion method. The results revealed that three endophytic fungal isolates produced inhibition zones, with the highest average diameter of 17.46 mm against Staphylococcus aureus and 18.66 mm against Staphylococcus epidermidis. These findings indicate the potential of betel leaf endophytic fungi as a natural source of antibacterial agents. This study underscores the role of endophytic fungi in developing new antibiotics to combat bacterial resistance.